If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 = 8x(3 + y) 96 = (3 * 8x + y * 8x) 96 = (24x + 8xy) Solving 96 = 24x + 8xy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 96 + -24x = 24x + -24x + 8xy Combine like terms: 24x + -24x = 0 96 + -24x = 0 + 8xy 96 + -24x = 8xy Add '-8xy' to each side of the equation. 96 + -24x + -8xy = 8xy + -8xy Combine like terms: 8xy + -8xy = 0 96 + -24x + -8xy = 0 Add '-96' to each side of the equation. 96 + -24x + -96 + -8xy = 0 + -96 Reorder the terms: 96 + -96 + -24x + -8xy = 0 + -96 Combine like terms: 96 + -96 = 0 0 + -24x + -8xy = 0 + -96 -24x + -8xy = 0 + -96 Combine like terms: 0 + -96 = -96 -24x + -8xy = -96 Reorder the terms: 96 + -24x + -8xy = -96 + 96 Combine like terms: -96 + 96 = 0 96 + -24x + -8xy = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(12 + -3x + -1xy) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(12 + -3x + -1xy)' equal to zero and attempt to solve: Simplifying 12 + -3x + -1xy = 0 Solving 12 + -3x + -1xy = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -3x + -12 + -1xy = 0 + -12 Reorder the terms: 12 + -12 + -3x + -1xy = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -3x + -1xy = 0 + -12 -3x + -1xy = 0 + -12 Combine like terms: 0 + -12 = -12 -3x + -1xy = -12 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -35-6m=-5(3m+2)+4m | | Y=-4.9t^2+45 | | 5x+2-6x-10=1x+520 | | -(n-2)-n=14-4n | | 8.4+10x=7 | | 7p-30=-1+5(3p+7) | | log(3)(x-5)=5 | | -6+2n=4(1+n) | | 4c^3-8c^2+1+5c^3+5c^3+19c+3= | | 2x-6[3-5x]=5 | | -30x+42=6(x+9) | | 180-x+12=2x | | -1/3M=12 | | 180-2x=X+12 | | 42=5z+12 | | -3(x+8)=x+4 | | 4n+8-2n=2n-5 | | Y=-xsquared+12x-5 | | (x-10)^2/3=-6 | | 8x+35=30x+24 | | -3/4b27 | | c/8=27 | | Y=4xsqrt(x) | | x^2+y^2-7x-5y+40=0 | | 4(x-7)+5x-2=-3 | | 6(x+8)=48 | | 7/8x=-2/3 | | 4x-25=5x | | 4d+6-6d=120 | | a+54=69 | | 1/2y=6x-5/9 | | -2y^2-7y+39=0 |